In Silico Analysis of Curcuma longa Against PCAF Histon Asetiltransferase - Artha Vinsentricia; Djarot Sasongko Hami Seno; Maria Bintang (IPB University, 2015)
Curcumin turmeric (C. longa) has been found capable of inhibiting p300/CBP associated factor (PCAF) histone asetyltransferase (HAT) as a cancer biomarker. However, the molecular mechanism of inhibition is unkown. This study is aimed to analyse the molecular inhibition mechanisms by in silico method. The analysis showed that curcumin’s Gibbs free energy (ΔG) was stable and capable of binding amino acid residues believed to be active site of PCAF HAT. Curcumin is predicted to be a PCAF HAT inhibitor, and further in vitro analysis is required.